Vaccine refusal and hesitancy in Spain: an online cross-sectional questionnaire - Agnes Huguet-Feixa; Eva Artigues-Barberà; Joaquim Sol; Xavier Gomez-Arbones; Pere Godoy; Marta Ortega Bravo (BMC Primary Care)
Abstract Background Vaccine refusal and hesitancy represent a crucial challenge to public health, causing delays in vaccination and compromising herd immunity. Methods To address this issue, we conducted a comprehensive observational study on the adult Spanish population in 2021. Using an online questionnaire, we examined the sociodemographic and sociocultural factors, beliefs, and opinions of those refusing or hesitant about vaccines, as well as their vaccination behaviors by vaccine type and sex. Results There were 1,312 respondents: 74.5% were female, 73.7% were between 31 and 59 years old, and 71.0% had university studies. Our findings revealed that vaccine refusal rates were relatively low (16.8%), and mainly associated with influenza vaccination (10.3%). Higher refusal rates were observed in those over 60 years old, those expressing hesitancy due to vaccine components, those opposing free and compulsory vaccination, those unaware that vaccination protects the community, and those against consuming cow’s milk and using infant formulas for breastfeeding. Vaccine hesitancy was greatest in individuals under 31 years old, women, parents of children under 15 years old, against compulsory vaccination, unaware that vaccination protects the community, with hesitancy due to vaccine costs, and in favour of alternative and complementary treatments. Conclusions These insights highlight the need for strategies to improve education about vaccination and dispel misconceptions, which are crucial for effectively reducing vaccine refusal and hesitancy across the population.